1982
DOI: 10.1530/acta.0.1000077
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two independent effects of oestradiol benzoate on the renin-angiotensin-aldosterone system

Abstract: Abstract. Plasma renin concentrations (PRC), plasma renin substrate concentration (PRS), plasma aldosterone and cortisol concentrations as well as plama renin activity (PRA) were measured in ovariectomized subjects after im administration of 10 mg oestradiol benzoate (EB). The esterified oestrogen exerts two independent effects on the renin-angiotensin-aldosterone system. 1) 48 h after EB administration, PRS was significantly increased. Similar results were obtained for total plasma cortisol, reflecting transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This finding is in agreement with Menard and Call [28] who have shown that estradiol treatment in rats produced a rapid increase within 6 h of plasma renin substrate and that following a transient 48-hour increase, plasma renin activity fell slightly below normal levels by day 6 when plasma renin concentrations were reduced by half. Although conflicting results have been published [for review see 33], it can be generally con cluded that in man, estrogens increase circulating All [5] and plasma renin activity [22,23]. These values approach normal levels with chronic treatment as plasma renin con centrations are being suppressed [23, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with Menard and Call [28] who have shown that estradiol treatment in rats produced a rapid increase within 6 h of plasma renin substrate and that following a transient 48-hour increase, plasma renin activity fell slightly below normal levels by day 6 when plasma renin concentrations were reduced by half. Although conflicting results have been published [for review see 33], it can be generally con cluded that in man, estrogens increase circulating All [5] and plasma renin activity [22,23]. These values approach normal levels with chronic treatment as plasma renin con centrations are being suppressed [23, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…30]. Several re ports [23,30] have suggested that in rats chronically treated with estradiol, homeostatic mechanisms are more efficient in compensating for increased plasma renin substrate than in women taking oral contraceptives or estrogens. It must be emphasized however, that discrepent results may be due to the use of pharmacological doses of estrogens in rats compared to much smaller therapeutic doses used in women.…”
Section: Discussionmentioning
confidence: 99%